Simultaneous Presentation of Wilms' Tumor and Contralateral Ganglioneuroma in a Child: Case Report and Literature Review. Issue 6 (August 2018) - Bayramoglu, Zuhal; Adaletli, Ibrahim; Caliskan, Emine; Kilicaslan, Isin; Karaoglan, Cagla S.; Celik, Alaattin; Gun Soysal, Feryal; Bay, Sema B.; Zulfikar, Bulent
Abstract : We demonstrate a 4-year-old girl who presented with progressive, asymmetrical, firm abdominal distention and was diagnosed with synchronous Wilms' tumor and left para-aortic ganglioneuroma (GN). Although synchronous tumors in the pediatric population are commonly associated with malignancy-predisposing syndromes, the patient in question was found to be otherwise healthy and had no clinical evidence nor family history of a syndrome. This case is the second one in the literature diagnosed with synchronous presentation of Wilms' tumor and GN in a previously healthy child. In addition, a GN foci presumed to be a previous metastasis of a neurogenic tumor that subsequently matured to GN was depicted within a left para-aortic lymph node. We aimed to emphasize an extremely rare synchronous occurrence of these embryonal tumors, increase the awareness of physicians, and discuss the radiologic differential diagnosis and management.